2022
DOI: 10.3390/jpm12071122
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Plasma Interleukin-6 Levels on Atherosclerotic Cardiovascular Disease and Cardiovascular Mortality Risk Scores in Javanese Patients with Chronic Kidney Disease

Abstract: Interleukin-6 (IL-6) has been identified as an important pro-inflammatory factor involved in mediating the severity of chronic kidney disease (CKD). This study sought to determine the effect of plasma IL-6 levels on atherosclerotic cardiovascular disease (ASCVD) and cardiovascular mortality risk scores in Javanese CKD patients. We also analyzed the frequency of IL-6 G174C single nucleotide polymorphism (SNP) in the population. This study was a cross-sectional study involving seventy-three patients of Javanese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 74 publications
1
6
0
2
Order By: Relevance
“…In European (Italian) patients with stage 2–5 CKD, high serum IL-6 was associated with a history of cardiovascular disease and predicted incident cardiovascular events, and this relationship was accompanied by the G174C polymorphism in the IL-6 gene [ 80 ]. This finding has been corroborated in other ethnicities [ 81 ]. Large-scale analyses from the UK Biobank have shown that genetic differences in IL-6 signalling preferentially modified the coronary artery disease risk to a greater extent among those with CKD than without [ 82 ].…”
Section: Inflammation In Crs ( Figure 2 )supporting
confidence: 82%
“…In European (Italian) patients with stage 2–5 CKD, high serum IL-6 was associated with a history of cardiovascular disease and predicted incident cardiovascular events, and this relationship was accompanied by the G174C polymorphism in the IL-6 gene [ 80 ]. This finding has been corroborated in other ethnicities [ 81 ]. Large-scale analyses from the UK Biobank have shown that genetic differences in IL-6 signalling preferentially modified the coronary artery disease risk to a greater extent among those with CKD than without [ 82 ].…”
Section: Inflammation In Crs ( Figure 2 )supporting
confidence: 82%
“…These enzymes operate within the window of intervention to reduce oxidative stress (WPOS). This is because cells experience a pseudo-healthy state of oxidative stress, characterized by levels between normal oxidative stress and those generated by disease, which can demonstrate beneficial effects when antioxidants are administered over time [10]. The doses used in this study align with those utilized in previous studies.…”
Section: Hypoxiamentioning
confidence: 94%
“…IL-6 and CRP play important roles in forming CAD plaques [17,26,[78][79][80]. CRP is a major parameter for treating CAD patients with periodontitis [17,81,82]. In contrast, CRP is not associated with periodontitis and CAD risk [49,58,83,84].…”
Section: Il-6 and Crp Levelsmentioning
confidence: 99%